Новый вид рода Systole (Hymenoptera, Eurytomidae) из Северного Приазовья - Зерова, М.Д.; Артохин, К.С. (Вестник зоологии, 1983)
Systole singularis Zerova sp. n.—similar to S. conspicus Erd.— differs by a head narrowed toward mouth edges, antennal structures in both sexes and
forewing venation. From all other Systole species differs by unusually elongated Ist segment of the female antennal flagellum. Larvae of the new species develop within Archangelica officinalis Hoffm. seeds.